2001
DOI: 10.1038/sj.leu.2402306
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of somatic mutations in proliferating T cell clones from children treated for leukemia

Abstract: There is continued controversy as to the sequential steps and mechanism(s) responsible for the in vivo acquisition of multiple mutations during neoplastic transformation. We investigated the in vivo clonality and mutational spectra of hypoxanthine-guanine phosphoribosyltransferase (HPRT) mutations in T cells from children with acute lymphocytic leukemia (ALL) to gain insight into the mutagenic mechanisms associated with leukemogenesis. We observed several instances of multiple, independent HPRT mutations accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We investigated the number of unique mutations in each subject sample by determining both the sequence of the TCRh CDR3 gene region as well as the specific HPRT mutation for each T cell HPRT mutant. This approach allows us to determine the extent of pre-or postthymic clonal proliferation, and allows calculation of the frequency of unique HPRT mutations (13). Analysis included 540 mutants (2-10 per sample) characterized from 71 blood samples from 42 subjects, in which some were represented in more than one phase of therapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We investigated the number of unique mutations in each subject sample by determining both the sequence of the TCRh CDR3 gene region as well as the specific HPRT mutation for each T cell HPRT mutant. This approach allows us to determine the extent of pre-or postthymic clonal proliferation, and allows calculation of the frequency of unique HPRT mutations (13). Analysis included 540 mutants (2-10 per sample) characterized from 71 blood samples from 42 subjects, in which some were represented in more than one phase of therapy.…”
Section: Resultsmentioning
confidence: 99%
“…We observed 15 examples of postthymic proliferation and 3 examples of ''proliferative'' clonality (ref. 13; same TCR and different HPRT mutations) from 12 of 38 children during treatment. During therapy, there were also six instances of clonality from four children in which the particular type could not be determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we do have the ability to address these questions by studying the relationship among HPRT-mutational spectra, cell proliferation, and selection through the use of TCR␤ gene analysis of each mutant isolate as an independent marker of clonality. We have previously used this relationship to demonstrate that in a subset of children treated for ALL, there is evidence of the emergence of both genomic instability and clonal proliferation (39,40). In the later study, we reported on the extent of clonal proliferation of HPRT-mutant isolates from 12 children treated for ALL who had Mfs Ͼ 30-fold higher than age-matched controls.…”
Section: Discussionmentioning
confidence: 96%